Anatomy of Tianjin Port fire and explosion: Process and causes. Issue 3 (26th July 2016) - Fu, Gui; Wang, Jianhao; Yan, Mingwei
Abstract : An investigation was performed into the Tianjin Port fire and explosion accident. It mainly focused on the process and causes. Initially, nitrocellulose burned spontaneously and the fire resulted in two major explosions of hazardous chemicals (mainly ammonium nitrate). Rough handling during the moving, loading and unloading of nitrocellulose directly resulted in the spontaneous combustion. Specifically, stacking various hazardous chemicals in the same area and storing ammonium nitrate in the port without permission caused the spread of the fire and the two major explosions. The implementation of Ruihai Company's management system (e.g., the safety training, safety supervision, etc.) for storage and transport of hazardous chemicals was deficient, and they neglected the importance of safety during production. Periodic safety inspection (e.g., the hazard identification, storage plan of hazardous chemicals, management system weaknesses, etc.) from local government agencies was not adequate and rigorous. Following accidents, casualties can be reduced or even avoided through adequate evacuation and rescue. Lessons can be learned from this disaster to avoid similar mistakes within the industry in the future. © 2016 American Institute of Chemical Engineers Process Saf Prog 35: 216–220, 2016